Re-examining the Rijksmuseum’s Oldest Ship Model: A 44-Gun Directorate Ship? - Odegard, Erik (The Rijksmuseum Bulletin, 2020)
The oldest ship model in the Rijksmuseum’s collection is of a Dutch warship with forty-four cannon. It has been suggested in the past that the model represents a ship that once belonged to one of the urban directorates which provided warships to escort merchant convoys in the first half of the seventeenth century. By combining archival and pictorial information, the article concludes that it is in fact improbable that the model depicts a specific ship belonging to one of the urban directorates. It is more likely that it is of an as yet unknown vessel, perhaps built for export, or that it is a generic model, designed to decorate the premises of the Amsterdam shipyard De Boot, whose owner ultimately donated the model to the museum in the nineteenth century, but which dates back to the sixteen-forties, the period in which the model was built.